Bhutan : Joint Staff Advisory Note of the Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2005)
This Joint Staff Advisory Note focuses on the Poverty Reduction Strategy Paper (PRSP) Progress Report for Bhutan. Bhutan's PRSP aims to galvanize the poverty reduction efforts of the Royal Government of Bhutan, building on past achievements. It targets an average growth rate of 8u percent during 2004/05-2006/07, which is about 1 3/4 percentage points above that experienced during the Eighth Plan and the first two years of the Ninth Plan. Pushing the economy to this higher growth trajectory will be a challenge; however, some increase in the growth rate can be expected over the medium term.